Water Quality of Bais Bay - Sa-a, Pascualita; Bustillo, Roy A. (Silliman Journal, 2023)
Secondary data on Bais Bay, and information derived from consultations with the Bais Bay community made apparent the issue of the Bay’s siltation and pollution prob-lem. Information gaps regarding the Bay were identified and these included the ab-sence of data on the sedimentation rate as well as the lack of information on the water quality and the nutrients in the sediment. The research activities on the water quality aspect of the marine component were geared toward addressing these gaps.